Knowledge of Postgraduate Research Scholars of Anand Agricultural University about GlobalWarming - J.B.Dobariya, N.B.Chauhan (Indian Journal of Extension Education, 2022)
Global warming has an impact on our planet, agriculture, human and animal lives. The future problems caused by global warming are raising sea water, growing deserts and more frequent droughts, all looks set to affect the developing world more than rich countries. In an effort to combat against global warming, issues related to agricultural development, agricultural research scholars as a future generation of agricultural development need to possess general awareness and knowledge about global warming issues and problems. Focused and timely efforts to apply knowledge by the agricultural research scholars can enable them to stand successfully against the global warming problems to play a leadership role in overall development of agriculture. The present study was undertaken on a random sample of 100 postgraduate research scholars studying in agriculture faculties of B. A. College ofAgriculture,AnandAgricultural University located atAnand of Gujarat state. Selected dependent and independent variables were measured with the help of suitable scale and procedures. The level of knowledge of the postgraduate scholarswas observed significantly higher among those who had higher academic performance, involvement in extracurricular activity, information collection habit, more than one occupation of family, elevated scientific orientation and positive attitudes towards integrated pestmanagement.